Retrocitomyia Lopes, 1982 (Diptera: Sarcophagidae): new species, new records, key to males, and an updated catalog - de Mello-Patiu, Cátia Antunes; Salazar-Souza, Mônica (Zootaxa, 2016)
Prior to this work, Retrocitomyia Lopes (Diptera: Sarcophagidae) included ten recognized species distributed exclusively in the New World. We here add a new species to the genus, Retrocitomyia sisbiota sp. nov. from the Central-West Region of Brazil. Four other species of Retrocitomyia are recorded from this region for the first time, redescribed, compared, and illustrated, with emphasis on the male terminalia. Retrocitomyia paraguayensis Lopes is recorded from Brazil for the first time, R. fluminensis Lopes and R. retrocita (Hall) are newly recorded from the Brazilian states of Mato Grosso and Mato Grosso do Sul, and R. mizuguchiana Tibana & Xerez is newly recorded from the state of Mato Grosso do Sul. New generic diagnostic characters are added and the interpretation of some structures of the male terminalia is discussed. An updated catalog of all Retrocitomyia species and an identification key to the males of these species are also provided.